Comparison of Vault Measurements Using a Swept-Source OCT-Based Optical Biometer and Anterior Segment OCT - Du, Yali; Jin, Chuang; Yin, Shengjie; Wang, Geng; Ma, Qian; Li, Yuancun; Chen, Binyao; Wang, Hongxi; Qiu, Kunliang; Zhang, Mingzhi (Frontiers in Medicine, 2022)
Background To newly describe the vault measurement by using a widely used swept-source OCT-based optical biometer (IOLMaster700) and accessd the accuracy of vault measurement. Methods This was a retrospective, cross-sectional study. All patients underwent implantable Collamer lens (ICL) implantation surgery without complications. IOLMaster700 and AS-OCT analyses were conducted for each eye on the same day in the same condition. Measurements of anterior chamber depth (ACD), corneal-ICL (C-ICL), and vault values were made and recorded. The repeatability of the IOL Master700 measurements was quantified based upon intraclass correlation coefficient (ICC) values. Correlations between IOL Master700 and AS-OCT measurements made with these different analytical approaches were assessed. The agreement of instruments was evaluated using Bland-Altman plots. Results The IOLMaster700 instrument yielded highly reliable measurements of vault, C-ICL, and ACD (ICC = 0.996, 0.995, 0.995, respectively). Vault, C-ICL and ACD values as measured using the IOLMaster700, was slightly smaller than that measured via AS-OCT, but these differences were not significant (p = 0.652, p = 0.121 and p = 0.091, respectively). The vault, C-ICL, and ACD measurements by these two instruments were strongly correlated (r = 0.971, r = 0.944, and r = 0.963, respectively; all p < 0.001). The 95% limits of agreement for vault, C-ICL, and ACD measurements between the two devices were−0.08 to 0.08 mm,−0.14 to 0.11 mm, and−0.13 to 0.10 mm, respectively. Conclusions The IOLMasrer700 can measure implanted ICL vault with a high degree of accuracy and repeatability. Good correlations and agreement were observed between IOLMaster700 and AS-OCT in measuring vault, C-ICL, and ACD measurements.